PD‐1 blockade using pembrolizumab in adolescent and young adult patients with advanced bone and soft tissue sarcoma. Issue 2 (13th December 2020) - Scheinberg, Tahlia; Lomax, Anna; Tattersall, Martin; Thomas, David; McCowage, Geoff; Sullivan, Michael; Karim, Rooshdiya; Luk, Peter P.; Mahar, Annabelle; Bonar, Fiona; Bhadri, Vivek A.
Abstract: Background: Sarcomas represent 10%–15% of cancers in adolescent and young adult (AYA) patients, and survival for those with metastatic disease or relapse is poor. Immunotherapy with checkpoint inhibition has improved outcomes in multiple tumor types, but data in advanced sarcomas, particularly within the AYA population, are limited. Aim: We aim to evaluate response and toxicity for AYA patients with sarcoma treated with pembrolizumab. Methods and results: We retrospectively reviewed AYA patients with advanced bone and soft tissue sarcoma who received self‐funded pembrolizumab between May 2015 and January 2019. Eighteen patients were identified. One patient with Ewing sarcoma had a sustained complete response to therapy. Two patients with alveolar soft part sarcoma received a clinical benefit from pembrolizumab: one had a radiological partial response with an excellent clinical response and one patient achieved stable disease. Four patients died of disease prior to first scheduled assessment and thus were not evaluable. The remaining eleven patients had progressive disease. Conclusion: The role of immunotherapy in AYA sarcoma warrants further investigation. Biomarkers of response need to be further evaluated in order to guide patient selection.